Family Frontiers: Insights into the experiences of having Medical-Technology-Dependent Children at Home - Mumtaz, Saba; Haroon, Zara; Abid, Mahnoor (Pakistan Journal of Humanities and Social Sciences, 2024)
The aim of this research is to explore the lived experiences of families providing care at home for medical technology dependent children focusing on its emotional, social and psychological impact along with highlighting how the family members cope with their daily challenges and the strategies they employ to maintain family wellbeing. Medical technology dependent children are those who require special health needs in terms of an external equipment to substitute for the loss of an essential bodily function or to ensure their survival. As an example, they need a complex treatment regimen using devise like mechanical ventilation or tracheotomy (Okido, Zago, & Lima, 2015). This research contributes to the existing literature by deepening the understanding of the caregivers’ challenges on looking after such children from a multifaceted perspective within the context of Pakistan. A phenomenological qualitative research design was used (Ho & Limpaecher, 2022). In-depth interviews were conducted from six families having a medical technology dependent child. The data was analyzed using an interpretative phenomenological analysis in a series of steps (Creswell & Poth, 2016). The analysis of the data yielded an overarching theme, major living challenges having the subthemes; psychological factors, social issues, and financial constraints.